The Analysis of the Effectiveness of Team Type Cooperative Learning Model Tournament (TGT) Based on the Snake and Ladder Game Media in Indonesian Literature Online Material during the Covid-19 Pandemic - Halimah Tussadiah; Mutia Febriyana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine (1) the validity of the development of the cooperative learning model type team games tournament (TGT) based on snake and ladder game media which is carried out online on Indonesian Literature material for students of the Indonesian Language Education study program, FKIP UMSU ?, and (2) the effectiveness of model development. Cooperative learning type team games tournament (TGT) based on snake and ladder game media which was carried out online on Indonesian Literature material for students of the Indonesian Language Education study program, FKIP UMSU. This research is a type of development research with a 4D model, namely define, design, develop, and disseminate. Data collection techniques in this study were carried out through observation, questionnaires, and tests. The research trial was carried out in Semester IV of the Indonesian Language Education Study Program. The results of the study proved that student learning outcomes reached 100% after being given the application of the team games tournament (TGT) learning model based on the snake and ladder game media. The results of the validity test by the validator show that the use of snake and ladder game media is valid and effective in online learning.